KOMPETENSI KEPRIBADIAN MAHASISWA PPL FTK UIN AR- RANIRY BANDA ACEH - Mashuri, Mashuri (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2018)
This study aims to describe the ability of students of the Tarbiyah and Teaching Faculties of UIN Ar-Raniry who carry out the Field Experience Practices (PPL) program in the High School of Bener Meriah Regency. This research is descriptive qualitative research that seeks to describe the results of research in accordance with the objectives of the study. The results showed that the personality competencies of students in the implementation of the Field Experience Practices (PPL) program in SMA Bener Meriah District in general were very well implemented (88.5%). With this acquisition will have a positive impact on students in the learning process. Especially in the context of increasing student learning motivation and also can have implications for the moral development of students. There are a number of aspects of personality competency which are (1) stable and stable personality aspects (93%), (2) adult behavior (89.1%), (3) stable and wise (86%), ( 4) authoritative (86%), and (6) noble and exemplary aspects (92%). However, even though the students have been able to practice very well, there is one aspect that needs to be improved in a better direction, namely one of the authoritative sub-aspects (students can be respected by students) only score 75%. Respected factors are very important to note, because if a teacher is not respected, especially by students, the learning process does not run optimally.